Management of multiple sclerosis patients in central European countries: current needs and potential solutions - Berger, Thomas; Adamczyk-Sowa, Monika; Csépány, Tünde; Fazekas, Franz; Hojs Fabjan, Tanja; Horáková, Dana; Illes, Zsolt; Klimová, Eleonóra; Leutmezer, Fritz; Rejdak, Konrad; Rozsa, Csilla; Šega Jazbec, Saša; et al. (Therapeutic advances in neurological disorders, 2018)
Multiple sclerosis (MS) experts in Europe are facing rapidly rising demands of excellence due to the increasing complexity of MS therapy and management. A central European expert board of MS experts met to identify needs and obstacles with respect to raising quality of MS care in central and Eastern European countries. There are substantial variations across countries regarding delivery of care and its cost structure, as well as access to treatment. To date, Eastern European countries are often less able to afford reimbursement of immunomodulatory agents than Western countries. Overall, approximately 40% of working-age patients are not working due to MS. Costs rise steeply with increasing disability; indirect costs constitute the bulk of the financial burden in patients with severe MS. Magnetic resonance imaging (MRI) assessment is meanwhile obligatory as the diagnostic interface in the management of MS patients. Recommended measures directed at improving quality of care include the collection of patient data in registries, enhanced education of healthcare professionals, implementation of national strategies aiming at reducing regional variation, optimization of approval processes, and removal of administrative barriers. Local partnerships with authorities such as those that represent the interests of employees can contribute to leverage the importance of epidemiological data. The need for education extends to (neuro)radiologists who are responsible for reporting MRI findings in expert quality. Dissemination of the Magnetic Resonance Imaging in MS (MAGNIMS) protocol would be an important step in this context. Also, clinical freedom of choice is rated as essential. Physicians should have access to a range of treatment options due to the complexity of disease. Guidelines such as the upcoming EAN-ECTRIMS clinical practice guideline also aim at providing a basis for argumentation in negotiations with national health authorities.
Keywords: burden of disease; access to treatment; quality of care; multiple sclerosis; MS registry